A Comparative Analysis and Evaluation of Specialist PPP Units' Methodologies for Conducting Value for Money Appraisals. Issue 3 (27th May 2017) - Boardman, Anthony; Hellowell, Mark
Abstract: Governments throughout the world are turning to public‒private partnerships (PPPs) as a means of providing new infrastructure. The decision to adopt a PPP over conventional government procurement is usually based on a value for money (VfM) appraisal, but this analysis is conducted differently in different countries. This article describes the correct way to conduct VfM analysis if the goal is to minimize the present value of the costs to the Treasury and if the goal is to maximize social welfare. It then compares the documented methodologies of nine specialist PPP units. It identifies four ways in which these methodologies depart from either of the correct approaches, and shows how each departure favors the PPP option. Finally, it shows how the UK approach might be augmented to determine the best value to society.